2000
DOI: 10.1159/000008766
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Hepatic Tissue Hypoxia Using Near Infrared Spectroscopy: Comparison with Hepatic Vein Oxygen Partial Pressure

Abstract: Hepatic hypoxia occurs during liver surgery and transplantation. The critical level associated with irreversible hepatocellular damage is unknown. Measurement of hepatic tissue oxygenation and hepatic vein oxygen partial pressure (HVPO2) reflects oxygen supply and consumption. Near infrared spectroscopy (NIRS) can be used to monitor hepatic oxyhaemoglobin (HbO2), deoxyhaemoglobin (Hb) and cytochrome oxidase (Cyt Ox) oxidation. This study compared regional hepatic tissue oxygenation (HbO Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
(45 reference statements)
0
29
1
Order By: Relevance
“…Of particular relevance to potential clinical applications were the data by ElDesoky and coworkers, who found a direct correlation between hepatic tissue hypoxia measured by liver surface NIRS in pigs and hepatic vein oxygen partial pressure during induced hypoxic hypoxemia. 11 However, in contrast to the promising animal experiments, our data show that, in children up to eight years of age, transcutaneously measured NIRS tissue oxygenation with an optode placed over the palpable liver does not correlate at all with the invasively determined SvhO 2 .…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Of particular relevance to potential clinical applications were the data by ElDesoky and coworkers, who found a direct correlation between hepatic tissue hypoxia measured by liver surface NIRS in pigs and hepatic vein oxygen partial pressure during induced hypoxic hypoxemia. 11 However, in contrast to the promising animal experiments, our data show that, in children up to eight years of age, transcutaneously measured NIRS tissue oxygenation with an optode placed over the palpable liver does not correlate at all with the invasively determined SvhO 2 .…”
Section: Discussioncontrasting
confidence: 92%
“…Several authors have reported on NIRS measurement of liver tissue oxygenation. [9][10][11][22][23][24][25] Most of these studies were performed in animals, with the NIRS probe attached to the liver surface after laparotomy. The investigators mainly studied relative changes of liver tissue oxygenation during naso-gastric feeding, induced hypovolemia, low cardiac output, graded hypoxia or hepatic vascular in-flow occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its oxygen extraction capacity approaches 100% during ischemia or hypoxia (34,35), the main mechanism for matching hepatic oxygen supply with need. There was a significant reduction of the HbT with severe hypoxia (FiO 2 ofՅ10%), which reflects the marked reduction in arterial blood flow due to the sympathetic vasoconstriction response to hypoxia (36,37).…”
Section: Discussionmentioning
confidence: 95%
“…Most of the work done in tissue oximtery involves near-infrared (NIR) spectra for measuring tissue oxygenation from deep tissue organs like the brain and the muscles [8][9][10]. Neverthless, few groups have investigated the potential of visible spectroscopy for a number of different clinical applications [11,12].…”
Section: Introductionmentioning
confidence: 99%